The Problem of Perpetuity in Cash Waqf - Yusep Rafiqi (UIN Sunan Gunung Djati Bandung, 2018)
In Indonesia, cash waqf began to emerge in recent years in line with the passage of the act of the Republic of Indonesia no. 41 Year 2004 About Waqf. But, in the act, money that can be donated as waqf property is almost certainly based on its nominal value rather than the real value. This article discusses how nominal or real value is contained in the currency when it is used as a waqf. The research approaches in this paper is qualitative description method through content analysis. This research analyzing the contents of various complexities between the opinion of fuqaha about cash waqf and its relevance to the act and economic empowerment of the ummah. By considering real value contained in the currency, cash waqf can only be executed with gold and silver criteria, not paper money criteria due to fluctuations in value. Thus, it is necessary to establish standardization of real value to gold and silver in the cash waqf.